ROMANTIC LOVE IN 'TWILIGHT': LOOKING AT THE ELEMENTS OF ROMANTICISM IN BELLA AND EDWARD'S RELATIONSHIP - Nisa, Zahrotun; Candraningrum, Dewi (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
The purpose of this study is to analyze the elements of romanticism contained in Bella and Edward's relationship in the film "Twilight", as well as to provide a deeper understanding of how the concept of romantic love is interpreted and realized in the context of modern literature. This research is descriptive qualitative and uses textual analysis as a data analysis technique. This research relies solely on secondary data, with the movie "Twilight" as the main source. Data collection is done through document analysis technique. The results show that Bella and Edward's romantic relationship in the movie "Twilight" is realized in several elements, including affection, trust, togetherness, and sharing time and activities. The depiction of the element of affection is stronger than other elements through scenes and dialog in Twilight. Romance in Twilight shows how love can bring sacrifice, affection, and intimacy, reflecting the complexity of the concept of romantic love in modern literature.